The zarzuelas of Salvador C. Magno conventions, imitations and originality. - Cruz-Lucero, Rosario
The years 1930 to 1940 are known to be the post zarzuela period, with vaudeville and the movies being the most popular theatrical forms, and the drama running closely behind. It was in this period, however, that Salvador Magno, the last Hiligaynon zarzuela writer, was at his most prolific and energetic, producing not less than thirty-nine zarzuelas and shuttling between Iloilo and Bacolod theaters with his Ilobac troupe., Magno straddled two cultural periods: the period of Filipinos' resistance to American colonialism (1900-1920) and the period of the Filipinos' gradual resignation to, and eventual acceptance of American neo-colonial culture (the 1930's). The zarzuelas of the earlier period, especially those described as "seditious, reflected the Filipinos' revolutionary spirit. Gradually, however, the zarzuela writers turned from revolutionary and patriotic themes to criticism of Filipino mores and manners. Even this critical element of the zarzuela dwindled to a purely melodramatic one, social problems merely being used as a springboard for tear-jerking situations. By the 1930's, the dominant entertainment forms were bodabil (adapted from the American vaudeville); The hollywood movie, which in turn was imitated by local movie-makers, and the drama, which was pure and simple melodrama. This thesis studies the zarzuela of Salvador C. Magno in the light of their peculiar position in the Ilonggo zarzuela tradition and in context of the social and cutural conditions obtaining in the period between 1930 and the outbreak of the Second World War. Because Magno stood at the end of the Ilongo zarzuela tradition, he was deeply influenced by the great zarzuela writers that came before him. However, because he stood within the transition period, his plays also reflected the culture change that his own generation was undergoing. This study on Magno's zarzuelas, therefore, aims to define his originality despite influences upon him; it shows how his zarzuela themes and forms reflect the culture change his generation was undergoing; and it attempts to define Magno's position in the Iloilo literary tradition. To achieve these aims, this thesis uses an inter-disciplinary approach, i.e., it studeis the works in the context of Magno's life, the literary tradition to which he belonged, and his socio-historical and cultural milieu. Its analysis of the Magno zarzuela is based on a tentative theory of the Iloilo zarzuela, which is abstracted from an investigation of the dramatic conventions commonly used by the Iloilo zarzuela writer and of the standards set by the zarzuela audiences and critics as derived from newspaper articles of the period and from interviews. The period of the Iloilo zarzuela was 1903-1930, when the Iloilo sugar industry reached its peak. The Iloilo zarzuela audience was composed of aristocratic art lovers, middle class wage-earners, and laborers of the seaport and the sugar plantations. There was a demand among critics and audiences that the zarzuelas contain realism and seriousness of purpose, besides the element of entertainment. These elements were often translated into the zarzuela as criticism of American colonialism or of the economic and political conditions in the country. The comic element was made to serve as a satirical comment on the foibles of Iloilo society. By 1930, the theaters were overrun by vaudeville, cinema. and romantic-escapist drama. The zarzuela became obsolete, not only because of the rise of these other theatrical forms, but principally because the country had begun to accept American neo-colonial culture and its consequent social and political diseases. Social criticism, which was the primary function of the zarzuela, was no longer possible and escaoist entertainment suited the public taste. Moreover, industrialization in Iloilo sparked off labor problems, especially in the sugar industry, and eventually brought about Iloilo's economic decline. In 1930 Borromeo Lou, the Filipino vaudeville king, came to Iloilo for a thre-month run. It was for Lou's jamboree show that Magno began to write and produce his zarzuelas. When this season ended, Magno formed the Ilobac troupe, which for the next decade travelled between Iloilo and Bacolod theaters to either perform in double programs with movies, or to be part of town fiesta entertainments. It was solely through these earnings that he raised a family of seven children in modest comfort. Magno, capitulating to public taste and reflecting the neo-colonial values of his period, produced domestic melodramas. His characters generally consisted of the philandering or unreasonable possessive husband, the wronged but persevering wife, a scheming mistress or mother -in-law, and the golden-hearted bailarina (cabaret dancer). The comic characters, usually a male and female servant, doled out pure farce, often of the lowest kind. Nevertheless, the dramatic situation was made to spring from social realities, especially the dilemmas engendered by the culture upheaval of the period. But when Magno deliberately attempted to write plays of social criticism, he would flounder and end the play with a condemnation of social protest and the injunction to conform. Thus, such plays all the more emphasized his generation's conformism and complacency. Magno, as a youth, had been an actor in the zarzuela troupe of Valente Cristobal, acknowledged "dean of the Hiligaynon zarzuela" in the period 1903-1930. Cristobal was also the greatest influence on Magno, who copied not only Cristobal's directing style, but also some of his zarzuela plots. A comparative analysis of a Cristobal play and Magno's adaptation reveals the essential difference between the two plays. Character development in Magno's play is fuller and characterization is more detailed. Moreover, he is more didactic, thus sacrificing language and logic of structure. The language of Cristobal's play is more lyrical, his songs containing striking imagery. Magno's choice of Cristobal'a melodramas as his models shows the romantic-escapist spirit of his period. It was in magno's age, the 1930's that American religious, education, economic, and political institutions were firmly transplanted into Philippine culture. The zarzuela, as a play of social realism, necessarily became obsolete; it had to shift its emphasis from social criticism to melodrama and farce in order to make itself acceptable to the new Filipino sensibility. Magno, zarzuela writer from 1930 to 1946, used the zarzuela form and conventions to reflect this now sensibility, which in turn left its mark upon the Hiligaynon literary tradition.